2006
DOI: 10.2106/jbjs.d.02996
|View full text |Cite
|
Sign up to set email alerts
|

Latissimus Dorsi Tendon Transfer for Irreparable Posterosuperior Rotator Cuff Tears

Abstract: Synchronous in-phase contraction of the transferred latissimus dorsi is a variable finding following the surgical treatment of irreparable posterosuperior rotator cuff tears, but when it is present it is associated with a better clinical result. Preoperative shoulder function and general strength influence the clinical result. Female patients with poor shoulder function and generalized muscle weakness prior to surgery have a greater likelihood of having a poor clinical result.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
82
2
18

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(108 citation statements)
references
References 2 publications
6
82
2
18
Order By: Relevance
“…5). The gain in active elevation is high (+70°) while the gain in active external rotation (+36°) is similar or superior to that reported with the standard two-incision procedure [1,2,11,18,23,30,35,47]. As observed in our early experience with the RSA, without the tendon transfer patients would remain disabled, because in the absence of external rotator cuff muscles (infraspinatus and teres minor) there is no counterbalance to the strong functional internal rotators (pectoralis major, latissimus dorsi, teres major and subscapularis).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…5). The gain in active elevation is high (+70°) while the gain in active external rotation (+36°) is similar or superior to that reported with the standard two-incision procedure [1,2,11,18,23,30,35,47]. As observed in our early experience with the RSA, without the tendon transfer patients would remain disabled, because in the absence of external rotator cuff muscles (infraspinatus and teres minor) there is no counterbalance to the strong functional internal rotators (pectoralis major, latissimus dorsi, teres major and subscapularis).…”
Section: Discussionsupporting
confidence: 65%
“…None of our patients could control the spatial positioning of their arm, as demonstrated by positive preoperative dropping, lag, and hornblower signs. Review of the literature suggests the reported gain in active external rotation after an isolated transfer of the LD is modest, but patient satisfaction remains high because the arm is stabilized by the transfer [1,2,18,23,30,35,47]. Gerber [19] has recently reported a similar series of patients treated with a LD transfer and reverse shoulder arthroplasty; his preliminary results suggested similar promise but demonstrated a lower gain in external rotation.…”
Section: Discussionmentioning
confidence: 99%
“…1,18,20,41 Transfer of the latissimus dorsi has been shown to be a viable option for the treatment of posterosuperior cuff tears in a selected group of patients. 2,8,22,24,25,31,34,38,50 For treatment of irreparable supraspinatus tears, the deltoid flap represents another possible treatment option. It was first described by Takagishi 44 in 1978 in Japan.…”
mentioning
confidence: 99%
“…43 Multiple authors have concurred that it is a valuable treatment option for painful or pain-free pseudoparalysis of external rotation provided that the subscapularis is intact. 17,41,52,59,74,101 Results are better if there is no chronic pseudoparalysis of anterior elevation and if the teres minor does not show advanced fatty infiltration. 21,41 Pectoralis major transfer Pectoralis major transfer either above 93,106 or below 82 the conjoined tendon is a valuable salvage procedure for isolated, irreparable subscapularis lesions.…”
Section: Latissimus Dorsi Transfermentioning
confidence: 99%